Sinkronasi Konsep Pemaafan Hakim Sebagai Wujud Asas Restorative Justice Dalam Hukum Acara Pidana - Ayu Dian Ningtia; Ahmad Faris Shofa (Jurnal Risalah Hukum, 2024)
The development of the criminal system does not only rely on the punishment of defendants, but has led to aligning the interests of victim recovery and defendant accountability by using a restorative justice approach; that the restorative justice approach has not been sufficiently regulated in the criminal justice system, especially regarding the types of cases, conditions and procedures for its application at the trial level to decisions containing a restorative justice approach. Several provisions in the 2023 Criminal Code are considered to need to be harmonized with the 1981 Criminal Procedure Code and the 2012 RKUHAP, one of which is the concept of judge forgiveness (rechterlijk pardon). Regarding these provisions, neither the 1981 KUHAP nor the 2012 RKUHAP have regulations regarding the mechanism for implementing social work crimes and supervision crimes, including ministries/agencies or parties involved in its implementation. This normative juridical research is intended as a recommendation to strengthen the implementation of judge forgiveness as a form of restorative justice by making the necessary adjustments to criminal procedural law reform in Indonesia to ensure the criminal justice system continues to run effectively, fairly and justly. in accordance with applicable legal principles. including in accordance with material provisions.